Genetically Induced Mouse Model for Colon-specific Epithelial Cell Tumorigenesis Driven by Loss of K8 and Apc - Tayyab, Mina; Minkkinen, Mira M. E.; Stenvall, Carl-Gustaf A.; Polari, Lauri; Nielsen, Victor; Shah, Yatrik M.; Toivola, Diana M. (Elsevier BV, 2026)
BACKGROUND & AIMS: Loss of keratin 8 (K8) has been shown to increase susceptibility towards colonocyte hyper-proliferation and tumorigenesis. However, most colorectal cancer (CRC) mouse models require carcinogen, develop small intestinal tumors, or have a long latency period. The aim was to establish a genetic, colon-specific, and more human-like CRC model driven by loss of K8 and adenomatous polyposis coli (Apc).
METHODS: Colon-specific targeting using CDX2P-CreERT2 mice was used to generate K8flox/flox; CDX2P-CreERT2 and K8flox/flox; CDX2P-CreERT2; Apcflox/+ mice. Disease activity was monitored, and colon was analyzed for tumor burden and histopathology over time. Keratin expression, inflammation, proliferation, cell polarity, colonocyte populations, and cell division symmetry were assessed using immunoblotting and immunofluorescence analysis. This data was compared with K8 expression analysis in patients with CRC and in UALCAN database.
RESULTS: K8flox/flox; CDX2P-CreERT2 mice develop mild diarrhea and express reduced K8 and partner keratins in a mosaic pattern in the colonic epithelium. K8-negative colon areas display increased crypt loss and more inflammation predominantly in the proximal colon. Increased colonocyte proliferation is observed throughout the colon. Impaired cell polarity and higher number of stem and progenitor cells with a shift towards asymmetric cell division in K8-negative areas of the distal colon highlight a pro-tumorigenic environment. Mice with additional monoallelic Apc inactivation show colon tumorigenesis and epithelial to mesenchymal transition distally. In patients with CRC, tumor K8 expression is decreased independent of disease type and stage, age, or gender.
CONCLUSIONS: Genetic colon-specific mouse model with loss of K8 and Apc adequately resembles human CRC. This study identifies anti-tumorigenic protective roles of colonocyte K8 in the colon.